Complications and Outcome of Children Presenting with Tuberculosis Meningitis - Tahreem Amjad, Tahira Nazir, Sanaullah, Urwa Khalil, Muhammad Anwar, Shazia Siddique, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of complications and outcome in children with tubercular meningitis. Study design: Descriptive case series. Place and duration of study: Department of Paediatric Medicine, The Children’s Hospital and Institute of Child Health Lahore from 1st July 2021 to 31st December 2021. Methodology: One hundred and forty children of both genders aged between 1-12 years diagnosed of tuberculous meningitis which were treated as per department protocols and were evaluated for various complications of TBM; seizures, tuberculoma, tuberculous brain abscess and hydrocephalus. Outcome of these children was evaluated after 3 months in terms of death and survival with and without sequelae; cognitive impairment, motor deficit, aphasias and seizures. Results: The mean age of the children was 4.9±2.6 years with 88(62.9%) boys and 52 (37.1%) girls. Among the various complications of TBM, tuberculoma was the most frequent and was observed in 73(52.1%) children followed by hydrocephalus 53(37.9%), seizures 20(14.3%) and tubercular brain abscess 11(7.9%). 16(11.4%) children died while 124(88.6%) children survived of TBM. Out of 124 children who survived, 72(58.1%) children had sequelae. Practical implication: Understanding the complication and related outcomes can assist in pre-empting the related issued in cases of tuberculosis meningitis and therefore assist in better treatment by promptly preventing sever complications identified through this research. Conclusion: Tuberculoma and hydrocephalus were observed as the most frequent complications in children presenting with tuberculous meningitis and majority of these children survived with long term disability. Keywords: Extrapulmonary tuberculosis, Tuberculous meningitis, Complications, Outcome